PENGARUH BELIS DALAM MASYARAKAT SUMBA - Steven, Christofan Dorry; Yunanto, Taufik Akbar Rizqy (Universitas Muhammadiyah Jember, 2019)
Belis is an obligation that must be completed by man when he wants to propose Sumba?s woman. Belis was identical by the surrender of the mating assets brought while the proposal processed. Belis consist of mamuli, katana, and a number animals such as horses and buffaloes. Determination of the number of belis that must be prepared by the man to propose depends of negotiating or agreement, the social status, and marriage of the girl?s mother. If the handover be accepted, the woman must also prepare and carry a bola ngandi containing woven cloth, muti salak, ivory as a form of reply from the belis that will be given to the man. The values of the Belis and the Bola ngandi must be balanced so don?t causing humiliations to both families. Belis can have a psychological impact on the lives of individuals and their families. This impact can be seen in self esteem and self efficacy.